40MHz crystal oscillator design and simulation - Zong, Enze (Nanyang Technological University, 2024)
In recent years, as the advancing of the wireline communication, the demand for low noise, and highly integrated crystal oscillators is rapid growing. Fully integrated on-chip low- noise crystal oscillators (XO), utilizing switched-capacitor trimming arrays, can overcome frequency drift with temperature and time while meeting the wireline transceiver’s requirements for frequency accuracy. Therefore, crystal oscillators, with their ease of integration and cost-effectiveness, hold significant market potential as alternatives to expensive off-chip crystal oscillators. The crystal oscillator, serving as a crucial circuit in the front end of the wireline transceiver, directly influences the overall performance of the transceiver, including specifications such as phase noise. This thesis presents a highly integrated, low-noise single-ended crystal oscillator design with programmable gm cell amplifier and switched-capacitor via TSMC N3E process, for a precise reference clock signal to the PLL in the wireline transceiver. The proposed crystal oscillator operates at a frequency of 40MHz. Simulation results indicate that the maximum power consumption under stable operating conditions is 2.43mW. The worst phase noise at 10 kHz, 1 MHz, and 20 MHz is -127dBc/Hz, -144dBc/Hz, and -151dBc/Hz, respectively. The frequency tuning range is approximately 300 ppm. Over a temperature range of -40 °C to +125 °C, the frequency offset is within ±10 ppm after trimming.